2013
DOI: 10.1074/jbc.m113.514554
|View full text |Cite
|
Sign up to set email alerts
|

Trimeric Transmembrane Domain Interactions in Paramyxovirus Fusion Proteins

Abstract: Background: Mutations in transmembrane domains can affect activity of viral fusion proteins, but little is known about potential interactions between these domains. Results: Isolated paramyxovirus fusion protein transmembrane domains interact as trimers. Conclusion: Viral fusion protein transmembrane domains self-associate. Significance: Transmembrane domain associations may regulate stability of the prefusion conformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 68 publications
3
55
0
Order By: Relevance
“…Also, packaging of a heterologous glycoprotein may result in attenuation of the vector. Additional effects may occur: for example, evidence from several paramyxoviruses implicated the TM, CT, and other domains in modulating fusogenic activity, stability, and protein folding (17,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, packaging of a heterologous glycoprotein may result in attenuation of the vector. Additional effects may occur: for example, evidence from several paramyxoviruses implicated the TM, CT, and other domains in modulating fusogenic activity, stability, and protein folding (17,19).…”
Section: Discussionmentioning
confidence: 99%
“…During viral assembly, the CT is thought to interact with internal virion proteins to mediate packaging of the F protein into virions (16)(17)(18). Evidence from several paramyxoviruses implicated TM and CT in modulating fusogenic activity, stability, and protein folding (17,19).…”
mentioning
confidence: 99%
“…For example, self-assembly of paramyxovirus (43,44), influenza virus (45,46), and HIV (47) F-protein transmembrane domains was demonstrated experimentally and is considered a determinant for proper protein folding and fusion activity (44,47). Studies with class I vFMGs have shown that insertion of synthetic, soluble fusion peptides into the membrane can deform the lipid bilayer (48) and induce membrane fusion (49).…”
Section: Discussionmentioning
confidence: 99%
“…Vero-SLAM effector cells were transfected with plasmids encoding the DSP 1-7 dual-split protein (44), MeV H, and a mixture of F-encoding plasmids at the indicated ratios. Vero-SLAM target cells received plasmid DNA encoding the DSP 8-11 subunit.…”
Section: Methodsmentioning
confidence: 99%
“…The F protein then undergoes a coordinated series of conformational changes to its most stable form to promote membrane fusion (17)(18)(19)(20). Thus, binding of the attachment glycoprotein to the cellular receptor(s) is critical for triggering the fusion process (21,22).…”
mentioning
confidence: 99%